2008
DOI: 10.1583/08-2447.1
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Abdominal Aortic Aneurysms:Increased FDG Uptake Suggests Inflammation in the Aneurysm Wall

Abstract: FDG-PET/CT is a promising technique to identify inflammation of the aneurysm wall. Irrespective of aneurysm diameter, asymptomatic AAAs show more FDG uptake and more inflammatory activity in the wall than the non-dilated abdominal aorta of sex/age-matched controls. Future studies will be directed at the predictive value of increased FDG uptake for aneurysm wall strength, rupture risk, and the utility of FDG-PET/CT in assessing the effect of medical interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 23 publications
(27 reference statements)
4
65
1
Order By: Relevance
“…They compared the SUVmax between these two groups. Those with AAA had a significantly higher SUV-max compared to the control group (26). These findings were reproducible and reported by other groups as well (36,37 (23).…”
Section: Clinical Studies Of Fdg-pet Imaging Of Inflammation In Abdomsupporting
confidence: 89%
“…They compared the SUVmax between these two groups. Those with AAA had a significantly higher SUV-max compared to the control group (26). These findings were reproducible and reported by other groups as well (36,37 (23).…”
Section: Clinical Studies Of Fdg-pet Imaging Of Inflammation In Abdomsupporting
confidence: 89%
“…Therefore, functional imaging has been increasingly advocated, lately by the use of 18 F-FDG-PET. [10][11][12][13][14] The sensitivity of imaging techniques for detection and activity assessment in patients with A/CP depends on the stage Owing to the low n-number (n 5 3), treated aortitis patients were not included in the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, use of 18 F-FDG uptake on 50-minute to stratification patients with AA dissection may be useful for predicting short-term and mid-term prognosis and achieving better management (68). Additionally, many previous studies have shown that FDG in the AA group has higher uptake than that the normal aortic group (63,65,69 F-FDG samples (71). Therefore, 18 F-FDG might be a new pathway to study the mechanical of AA and to predict the risk of rupture.…”
Section: Metabolism Activitiesmentioning
confidence: 99%
“…Growing evidence show that an increase in 18 F-FDG uptake is a latent signal in the aorta with active atherosclerotic inflammation (59,60). Many studies have attempted to use 18 F-FDG to evaluate aortic diseases (61)(62)(63)(64)(65)(66)(67).…”
Section: Metabolism Activitiesmentioning
confidence: 99%